Piezo1 Promotes Odontogenic Differentiation of Dental Pulp Stem Cells Under Stress Conditions - Xiaxia Wang; Shaojie Dong; Qianqian Dong; Xuefei Sun (International Dental Journal)
Objectives: Mechanical stimuli signals regulate the odontogenic differentiation of dental pulp stem cells (DPSCs), but they are difficult to apply in clinical treatment. Piezo1, a specific mechanically activated ion channel that mediates mechanical transduction, may serve as a potential target for regulating mechanical signals. In the present study, we aimed to investigate the function and potential molecular mechanisms of Piezo1 in the odontogenic differentiation of DPSCs. Methods: Piezo1 expression in human dental pulp and DPSCs was detected by immunofluorescence or immunohistochemistry (IHC). The mechanotransduction of Piezo1 ion channels in DPSCs was determined by fluid shear stress (FSS) detection of calcium fluorescence intensity and whole-cell patch clamp detection. The role of Piezo1 in the odontogenic differentiation of DPSCs was detected by alizarin red staining and Western blotting under hydrostatic pressure (HP). The expression and distribution of the downstream molecules Piezo1, CaN, and YAP were detected through coimmunoprecipitation (co-IP), immunocytochemistry (ICC), and Western blot analysis. Results: The Piezo1 protein was positively expressed in human dental pulp samples, especially in the odontoblast layer. Increased Piezo1 expression was also detected after odontogenic differentiation of DPSCs in vitro. The fluorescence intensity of intracellular calcium ions (Ca2+i) increased rapidly with treatment with FSS or Yoda1 (a Piezo1-specific agonist) but did not significantly change after treatment with GsMTx4 (a Piezo1 antagonist) or BAPTA (an extracellular calcium ion chelating agent). A whole-cell patch clamp was used to record the inward current induced by mechanical stimulation of the DPSCs. After Yoda1 treatment, the peak current increased, but the currents nearly completely disappeared after pretreatment with GsMTx4. In addition, we found that blocking CaN or YAP reversed the ability of HP to promote DPSC odontogenic differentiation. Co-IP and ICC revealed that the CaN and YAP proteins colocalized and bound to each other in DPSCs. Conclusions: These findings indicated that the Piezo1 ion channel mediates the mechanical transduction of DPSCs. In addition, Piezo1 promotes odontogenic differentiation of DPSCs through the Ca2+/CaN/YAP signalling axis under HP, which provides effective intervention targets for mechanical stimulation-mediated regulation of reparative dentin and vital pulp preservation.